1, 25(OH)2D3 Mitigates Oxidative Stress-Induced Damage to Nucleus Pulposus-Derived Mesenchymal Stem Cells through PI3K/Akt Pathway. (18th March 2022) - Wang, Jun-wu; Zhu, Lei; Shi, Peng-zhi; Wang, Ping-chuan; Dai, Yan; Wang, Yong-xiang; Lu, Xu-hua; Cheng, Xiao-fei; Feng, Xin-min; Zhang, Liang
Abstract : Intervertebral disc degeneration (IVDD) is one of the main causes of low back pain. The local environment of the degenerated intervertebral disc (IVD) increases oxidative stress and apoptosis of endogenous nucleus pulposus-derived mesenchymal stem cells (NPMSCs) and weakens its ability of endogenous repair ability in degenerated IVDs. A suitable concentration of 1 α, 25-dihydroxyvitamin D3 (1, 25(OH)2 D3 ) has been certified to reduce oxidative stress and cell apoptosis. The current study investigated the protective effect and potential mechanism of 1, 25(OH)2 D3 against oxidative stress-induced damage to NPMSCs. The present results showed that 1, 25(OH)2 D3 showed a significant protective effect on NPMSCs at a concentration of 10 -10  M for 24 h. Protective effects of 1, 25(OH)2 D3 were also exhibited against H2 O2 -induced NPMSC senescence, mitochondrial dysfunction, and reduced mitochondrial membrane potential. The Annexin V/PI apoptosis detection assay, TUNEL assay, immunofluorescence, western blot, and real-time quantitative polymerase chain reaction assay showed that pretreatment with 1, 25(OH)2 D3 could alleviate H2 O2 -induced NPMSC apoptosis, including the apoptosis rate and the expression of proapoptotic-related (Caspase-3 and Bax) and antiapoptotic-related (Bcl-2) proteins. The intracellular expression of p-Akt increased after pretreatment with 1, 25(OH)2 D3 . However, these protective effects of 1, 25(OH)2 D3 were significantly decreased after the PI3K/Akt pathway was inhibited by the LY294002 treatment. In vivo, X-ray, MRI, and histological analyses showed that 1, 25(OH)2 D3 treatment relieved the degree of IVDD in Sprague– Dawley rat disc puncture models. In summary, 1, 25(OH)2 D3 efficiently attenuated oxidative stress-induced NPMSC apoptosis and mitochondrial dysfunction via PI3K/Akt pathway and is a promising candidate treatment for the repair of IVDD.